Reaction Wheel Torque Distribution Algorithm for Enhancing the Agility of the Spacecraft using Null motion. Issue 1 (2022) - Kumar K, Ashok; Aditya, R; Siva, M S
Abstract: Earth observation satellites require rapid attitude maneuvering and stringent pointing accuracy for imaging payloads. Four numbers of Reaction Wheel (RW) are usually configured in standard tetrahedral configuration for attitude manoeuvring as well as for fine pointing. The Reaction wheel maximum torque is one of the critical parameters that determine the agility of the spacecraft. Three axis attitude control torque signal is distributed to 4 Reaction wheels using standard pseudo inverse solution which minimizes the sum of the square of the individual wheel torque rather than the maximum of the individual wheel torque. The pseudo inverse solution leads to wheel saturation even when the total momentum does not reach the envelope and there by limiting the agility of the spacecraft. In this paper, new approach is adopted to optimally utilize the full capacities of RWs and thereby enhancing the agility of the spacecraft. The new algorithm is based on the null motion of the reaction wheel torque alignment matrix. The proper choice of the null vector results in equal wheel torque demand when combining with the pseudo inverse solution. The maneuver & control algorithms are integrated together with new distribution method and have been demonstrated for typical rest to rest and rate to rate maneuver.